2015
DOI: 10.1051/0004-6361/201525690
|View full text |Cite
|
Sign up to set email alerts
|

Microwave thermal emission from the zodiacal dust cloud predicted with contemporary meteoroid models

Abstract: Predictions of the microwave thermal emission from the zodiacal dust cloud are made using several contemporary meteoroid models to construct the distributions of the cross-section area of dust in space, and by applying the Mie light-scattering theory to estimate the temperatures and emissivities of dust particles in a wide range of sizes and heliocentric distances. In particular, the Kelsall model of the zodiacal light emission based on COBE infrared observations is extrapolated to the microwaves with assistan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…Here we also recall that the WMAP and Planck satellites made observations from Lagrange point 2 (L 2 ) while going round the Sun (in ecliptic plane) from behind the Earth. But it would be difficult to explain this in terms of a Solar System foreground (see section 4.1 of [211], and also [212]). Some of the higher order multipoles (ℓ > 3) of CMB sky were also found to be initially aligned with the quadrupole and octopole (besides CMB dipole) [204].…”
Section: Quadrupole and Octopole Alignmentsmentioning
confidence: 99%
“…Here we also recall that the WMAP and Planck satellites made observations from Lagrange point 2 (L 2 ) while going round the Sun (in ecliptic plane) from behind the Earth. But it would be difficult to explain this in terms of a Solar System foreground (see section 4.1 of [211], and also [212]). Some of the higher order multipoles (ℓ > 3) of CMB sky were also found to be initially aligned with the quadrupole and octopole (besides CMB dipole) [204].…”
Section: Quadrupole and Octopole Alignmentsmentioning
confidence: 99%
“…However, in our Solar system, zodiacal dust is much more extended than the habitable zone, and actually shows an increasing density down to the F-corona, with a possible dust-free zone within 0.1-0.2 au from the Sun (e.g. Dikarev & Schwarz 2015;Howard et al 2019). Likewise, it is expected that exozodiacal dust can extend over a broad range of separations from its host star, much larger than just the habitable zone.…”
Section: Introductionmentioning
confidence: 76%
“…Before finishing, it's worth recalling that IPDE models are fairly uncertain at these "long wavelengths" of interest to CMB experimenters. Dikarev & Schwarz (2015) have compared the Kelsall et al (1998) model with two other, more recent models and found significant differences. While their Divine (1993) and Dikarev et al (2005) models have less "structure" in them, the absolute level of the contamination is, in fact, estimated to be higher than that in the Kelsall et al (1998) model, and may, therefore, show more contamination in CMB maps (see also Jorgensen et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While IPDE did not significantly affect the Planck results, its existence did complicated some aspects of the Planck /HFI analyses. We must recognize that IPDE models are still very approximate, especially at long wavelengths (Dikarev & Schwarz 2015), and that the polarization properties of IPDE are still poorly constrained. But the ambitious LiteBIRD goals demand that we check that IPDE will not compromise the measurements.…”
Section: Introductionmentioning
confidence: 99%